Fuels from bio-oils: Bio-oil production from different residual sources, characterization and thermal conditioning - Bertero, Melisa Paola (2012)
Bio-oils from different residual biomass raw materials (pine wood, mesquite wood and wheat shell) were produced by means of conventional pyrolysis at a temperature of 550°C during 60 min. Bio-oils were separated from gases, tar and char, to show yields between about 30 wt.% and 45 wt.%, and fractionated into water- and ether-soluble fractions in order to know their compositions. Gas chromatography-mass spectrometry was used to identify compounds and complemented with elemental analysis and Conradson carbon residue (CCR), together with water content, density and pH assessments. The composition of the bio-oils varied according to the source biomass. Compounds were considered in eleven main groups: acids, esters, linear aldehydes and ketones, cyclic ketones, furans, alcohols and sugars, phenols, other oxygenated cyclic compounds, hydrocarbons, ethers and nitrogen compounds. The physicochemical properties of bio-oils suggested that it is necessary to upgrade them before co-processing in conventional refining units such as those of catalytic cracking of hydrocarbons. Thermal pre-treatments were conducted with the aim of reducing the CCR of the bio-oils, resulting in a significant average 70% reduction. The concentration of coke precursor phenolic compounds, mainly phenolic ethers, was reduced between 7% and 25%. Another important consequence was the increase in the effective hydrogen index of the mixture, suggesting higher processability in FCC.